Effect of Nano-TiO₂ Particles on Wear and Corrosion Behaviour of AA6063 Surface Composite Fabricated by Friction Stir Processing - Muthukrishnan, D.; Balaji, A.N.; Raghav, G.R. (Металлофизика и новейшие технологии, 2018)
In this investigation, the effect of nano-TiO₂ particles on wear and corrosion behaviour of AA6063 surface nanocomposites produced viavia friction stir processing (FSP) was studied. Microstructure analysis of fabricated surface nanocomposites was done with scanning electron microscope and found that TiO₂ nanoparticles are uniformly dispersed in the stir zone. The surface nanocomposites were characterized by hardness, wear and corrosion tests. The results revealed that the microhardness increases due to the presence of hard TiO₂ nanoparticles than as AA6063 alloy. The FSPed surface nanocomposites exhibited low frictional coefficient, excellent wear resistance and adequate corrosion resistance at 40 mm/min and as compared to that of the as cast alloy.